Common Patterns Of Occupational Injuries Dealt With By Saudi Red Crescent Paramedics (The Review of Diabetic Studies, 2025)
This research aims to highlight the common patterns of occupational injuries dealt with by paramedics of the Saudi Red Crescent Authority, by analyzing the nature of these injuries, the characteristics of the injured, and the work environments in which occupational accident rates are higher. Work-related injuries are among the most prominent challenges facing various professional sectors, due to their direct impact on workers' health and production efficiency, in addition to the pressure placed on emergency and ambulance response systems. The research relies on the descriptive approach by collecting data from field records and ambulance reports that were dealt with during a specific time period, with the aim of identifying the most common types of occupational injuries, such as falls, lacerations, fractures, burns, back injuries, in addition to injuries resulting from exposure to chemicals or sharp devices in the work environment. The research also addresses the factors that contribute to these injuries, including poor adherence to safety procedures, lack of training, and unsuitable environmental or technical conditions. The research also focuses on the quality of first aid interventions provided by paramedics at the scene of the accident, and the extent to which the speed of response affects the health outcome of the injured worker. The challenges faced by paramedics in dealing with occupational injuries are also discussed, such as the lack of information available on site, or the hazardous working environment upon arrival. This research is expected to contribute to providing a clear picture that will help enhance occupational safety programs, raise the readiness of ambulance teams, and propose effective mechanisms to reduce occupational injuries, thereby supporting the protection of workers and improving the quality of ambulance response within the Kingdom of Saudi Arabia.